(untitled) - 1962-; Wiseman, Beth (Nashville, Tenn., 2009)
After the death of her husband, Sadie Fisher's world is turned upside-down when the wealthy Kade Saunders rents her guest cottage, and as Sadie's feelings for Kade's five-year-old autistic son grow, so do her feelings for Kade.
Keywords: Amish; Fiction; Autism; Fiction; Fiction